Trans-perovskite solar cell with ultraviolet and water stability and preparation method thereof

By using specific green fluorescent protein chromophore derivatives in the hole transport layer and perovskite absorber layer of trans perovskite solar cells, the interface defects, energy level mismatch, ultraviolet and water stability of perovskite solar cells are solved, and efficient and stable photoelectric conversion efficiency is achieved.

CN119855359AActive Publication Date: 2025-04-18WUHAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411782310.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The buried interface layer of existing trans perovskite solar cells has problems such as defects, energy level mismatch, poor UV operation stability and poor water stability.

Method used

An ethanol solution of the green fluorescent protein chromophore derivative FLUO-C3-COOH was used as the second hole transport layer modifier, and a chlorobenzene solution extractant of FLUO-C10 with a hydrophobic long carbon chain was used to improve the stability of the perovskite light absorbing layer.

Benefits of technology

The photoelectric conversion efficiency, ultraviolet stability and water stability of perovskite solar cells are improved, ensuring the long-term stability and efficient performance of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005173073230000011
    Figure HDA0005173073230000011
  • Figure HDA0005173073230000012
    Figure HDA0005173073230000012
  • Figure HDA0005173073230000021
    Figure HDA0005173073230000021
Patent Text Reader

Abstract

The invention provides a trans-perovskite solar cell with ultraviolet and water stability and a preparation method thereof, and the cell sequentially comprises a transparent conductive substrate, a first hole transmission layer, a second hole transmission layer, a perovskite light absorption layer, an electron transmission layer, an interface modification layer, and a metal electrode layer from the bottom to the top. The first hole transport layer comprises NiOx, the second hole transport layer comprises FLUO-C3-COOH, and the perovskite light absorption layer comprises FLUO-C10. The perovskite thin film has the advantages of being smoother, small in defect density, fast in carrier transport and the like, and the whole perovskite solar cell shows excellent power conversion efficiency and good ultraviolet operation stability and water stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular, relates to an inverted perovskite solar cell with ultraviolet and water stability and a preparation method thereof. Background Art

[0002] Among many new energy sources, solar energy resources are the most abundant, cost-free and will not cause any burden to the ecological environment. It is recognized as the most promising energy source to replace traditional fossil fuels. Solar cells are one of the important solar energy utilization technologies, among which perovskite solar cells have attracted widespread attention due to their low cost, high efficiency and easy preparation. So far, the PCE of single-junction perovskite solar cells has increased from 3.8% in 2009 to 26.7% certified in 2024, which has exceeded those commercialized silicon-based counterparts and is approaching the Shockley-Queisser (SQ) limit. However, due to the presence of internal defects, the long-term stability of the perovskite light-absorbing layer is poor, especially under harsh operating conditions, which is still a severe challenge for the commercialization of perovskite solar cells.

[0003] Perovskite films prepared by solution method are prone to introduce a high defect state density, especially causing serious non-radiative recombination at the buried interface, resulting in reduced device efficiency and triggering film degradation under water, oxygen, high temperature and light, further deteriorating device stability.

[0004] In order to simultaneously reduce various defects in perovskites and enhance their adaptability to environmental conditions, and to construct highly stable PSCs, a large amount of research has been devoted to suppressing defect states in perovskites and improving the operational stability of devices under moisture, heat, and light through various strategies such as crystallization control, interface engineering, precursor engineering, and strain engineering. However, the important factor that high-energy ultraviolet radiation is severely destructive to the perovskite lattice has not received enough attention. Therefore, how to enhance the buried interface by improving the preparation process, improve the efficiency of perovskite solar cells, and improve the ultraviolet operational stability without losing other properties remains an urgent problem and challenge to be solved. Summary of the invention

[0005] In view of the above technical problems, especially for inverted perovskite solar cells, the purpose of the present invention is to solve the defects and energy level mismatch problems of the existing buried interface layer, i.e., the hole transport layer, as well as the poor UV operation stability and water stability of the perovskite solar cell, and provide an ethanol solution of a green fluorescent protein chromophore derivative FLUO-C3-COOH with UV conversion function as a hole transport layer modifier, and a green fluorescent protein chromophore derivative FLUO-C3-COOH with a hydrophobic long carbon chain as a hole transport layer modifier. 10The chlorobenzene solution extractant is used to solve the above problems, providing a method for preparing efficient and stable inverse perovskite solar cells, which have the characteristics of good hole transport layer film quality, uniform and dense perovskite film, high photoelectric conversion efficiency, good UV stability and water stability.

[0006] In one aspect of the present invention, the present invention discloses an inverted perovskite solar cell. According to an embodiment of the present invention, the inverted perovskite solar cell comprises, from bottom to top, a transparent conductive substrate, a first hole transport layer, a second hole transport layer, a perovskite light absorption layer, an electron transport layer, an interface modification layer and a metal electrode layer, wherein the first hole transport layer comprises NiO x The second hole transport layer includes FLUO-C3-COOH, and the perovskite light absorption layer includes FLUO-C 10 The perovskite film has the advantages of being flatter, having a lower defect density, and having faster carrier transport, and the overall perovskite solar cell exhibits excellent power conversion efficiency, good UV operation stability, and water stability.

[0007] According to an embodiment of the present invention, the inverse perovskite solar cell may further include at least one of the following additional technical features:

[0008] According to an embodiment of the present invention, the second hole transport layer is a MeO-4PACz film added with FLUO-C3-COOH.

[0009] According to an embodiment of the present invention, the perovskite light absorbing layer is a perovskite light absorbing layer with a green fluorescent protein chromophore derivative FLUO-C added thereto. 10 APbX3 thin film was prepared by extraction with chlorobenzene solution, where A is Cs + , methylammonium (MA + ) or methyl ether amine (FA + ), X is I - or Br - .

[0010] According to an embodiment of the present invention, the transparent conductive substrate is FTO conductive glass.

[0011] According to an embodiment of the present invention, the electron transport layer is PCBM.

[0012] According to an embodiment of the present invention, the interface modification layer is BCP.

[0013] According to an embodiment of the present invention, the metal electrode layer is a silver electrode layer.

[0014] In another aspect of the present invention, the present invention also provides a method for preparing an inverse perovskite solar cell. According to an embodiment of the present invention, the method comprises:

[0015] S1: NiO x The aqueous solution is spin-coated on a transparent conductive substrate and subjected to a first annealing treatment to obtain a first hole transport layer;

[0016] S2: Spin-coating a mixed solution of FLUO-C3-COOH and MeO-4PACz on the first hole transport layer, and performing a second annealing treatment to obtain a second hole transport layer;

[0017] S3: Spin-coat the perovskite solution onto the second hole transport layer with FLUO-C 10 The method is simple to operate, and the prepared film has the characteristics of good hole transport layer film quality, uniform and dense perovskite film, high photoelectric conversion efficiency, good ultraviolet stability and water stability.

[0018] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0019] According to an embodiment of the present invention, the method further comprises:

[0020] S4: spin coating the PCBM solution on the perovskite light absorbing layer, and performing a fourth annealing treatment to obtain an electron transport layer;

[0021] S5: spin coating the BCP solution on the electron transport layer, and performing a fifth annealing treatment to obtain an interface modification layer;

[0022] S6: evaporating a metal layer on the interface modification layer to obtain a metal electrode layer.

[0023] According to an embodiment of the present invention, the transparent conductive substrate is cleaned in advance.

[0024] According to an embodiment of the present invention, the cleaning process is performed in the following manner:

[0025] The transparent conductive substrate is first rinsed with deionized water and ultrasonically treated, and then placed in anhydrous ethanol, isopropanol, acetone and anhydrous ethanol in sequence for ultrasonic treatment; when used, it is blown dry with high-purity nitrogen and then treated with ultraviolet ozone.

[0026] According to an embodiment of the present invention, the transparent conductive substrate is FTO conductive glass.

[0027] According to an embodiment of the present invention, the transparent conductive substrate has a size of 1.5 cm x 1.5 cm.

[0028] According to an embodiment of the present invention, the NiOx NiO in aqueous solution x The concentration is 5-10 mg / ml. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0029] According to an embodiment of the present invention, the NiO x The aqueous solution was prepared as follows:

[0030] Nickel nitrate hexahydrate and ammonia water were dissolved in deionized water and stirred for reaction, and the product was centrifuged and washed three times with deionized water. The obtained product was vacuum dried and finally NiO was obtained in a muffle furnace. x Powder, NiO x The nanoparticles are dispersed in deionized water at a concentration of 5 to 10 mg / ml to obtain the NiO x Aqueous solution.

[0031] According to an embodiment of the present invention, the temperature of the muffle furnace is 250-300° C. If the temperature is not within this range, the efficiency of the solar cell device will be reduced.

[0032] According to an embodiment of the present invention, the spinning speed in step S1 is 3000-5000 rpm / s. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0033] According to an embodiment of the present invention, the spin coating time in step S1 is 30 to 60 seconds. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0034] According to an embodiment of the present invention, the temperature of the first annealing treatment is 100-200° C. If the temperature is not within this range, the efficiency of the solar cell device will be reduced.

[0035] According to an embodiment of the present invention, the time of the first annealing treatment is 30 minutes. If the time is not within this range, the efficiency of the solar cell device will be reduced.

[0036] According to an embodiment of the present invention, the NiO x The amount of the aqueous solution used is 40 to 60 ul. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0037] According to an embodiment of the present invention, the molar ratio of FLUO-C3-COOH to MeO-4PACz in the mixed solution of FLUO-C3-COOH and MeO-4PACz is 0.25%.

[0038] According to an embodiment of the present invention, the mixed solution of FLUO-C3-COOH and MeO-4PACz is prepared by the following method:

[0039] Ethanol solutions of FLUO-C3-COOH and MeO-4PACz of certain concentrations were prepared respectively, and the mixed solutions were obtained by mixing and stirring at a molar ratio of 0.25% between FLUO-C3-COOH and MeO-4PACz to obtain the mixed solution of FLUO-C3-COOH and MeO-4PACz.

[0040] According to an embodiment of the present invention, the spinning speed in step S2 is 3000-5000 rpm / s. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0041] According to an embodiment of the present invention, the spin coating time in step S2 is 30 to 60 seconds. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0042] According to an embodiment of the present invention, the temperature of the second annealing treatment is 100-150° C. If the temperature is not within this range, the efficiency of the solar cell device will be reduced.

[0043] According to an embodiment of the present invention, the second annealing treatment time is 10-20 minutes. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0044] According to an embodiment of the present invention, the amount of the mixed solution of FLUO-C3-COOH and MeO-4PACz is 40-50ul. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0045] According to an embodiment of the present invention, the perovskite solution includes FAPbI3, CsPbI3 and MAPbBr3.

[0046] According to an embodiment of the present invention, the perovskite solution is prepared by the following method:

[0047] FAPbI3, CsPbI3 and MAPbBr3 were respectively dissolved in a mixed solvent of DMF and DMSO in a volume ratio of 9:1 to prepare a perovskite precursor solution with a concentration of 1.3 mol / L. After sufficient dissolution, 3% molar concentration of CsPbI3 and 3% molar concentration of MAPbBr3 were added to the FAPbI3 solution to obtain the perovskite solution.

[0048] According to an embodiment of the present invention, the spinning speed in step S3 is 4000-6000 rpm / s. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0049] According to an embodiment of the present invention, the spin coating time in step S3 is 20 to 40 seconds. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0050] According to an embodiment of the present invention, in step S3, 150 to 200 μl of 0.15% mmol / ml FLUO-C is evenly and quickly added 1 to 5 seconds before spin coating. 10 The perovskite mesophase film is then transferred to a chlorobenzene solution for extraction and then subjected to a third annealing treatment.

[0051] According to an embodiment of the present invention, the temperature of the third annealing treatment is 100°C.

[0052] According to an embodiment of the present invention, the third annealing treatment lasts for 10 to 30 minutes. If the time is outside this range, the efficiency of the solar cell device will be reduced.

[0053] According to an embodiment of the present invention, the dosage of the perovskite solution is 45ul.

[0054] According to an embodiment of the present invention, the concentration of the PCBM solution is 20-40 mg / ml. If the concentration is not within this range, the efficiency of the solar cell device will be reduced.

[0055] According to an embodiment of the present invention, the PCBM solution is obtained by dissolving PCBM in a chlorobenzene solution.

[0056] According to an embodiment of the present invention, the spinning speed in step S4 is 2000-3000 rpm / s. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0057] According to an embodiment of the present invention, the spin coating time in step S4 is 20 to 40 seconds. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0058] According to an embodiment of the present invention, the temperature of the fourth annealing treatment is 70-100° C. A temperature outside this range may result in reduced efficiency of the solar cell device.

[0059] According to an embodiment of the present invention, the fourth annealing treatment lasts for 10-20 minutes. If the time is outside this range, the efficiency of the solar cell device will be reduced.

[0060] According to an embodiment of the present invention, the usage of the PCBM solution is 30ul.

[0061] According to an embodiment of the present invention, the concentration of the BCP solution is 0.5-1 mg / ml. If the concentration is not within this range, the efficiency of the solar cell device will be reduced.

[0062] According to an embodiment of the present invention, the BCP solution is obtained by dissolving BCP in trifluoroethanol.

[0063] According to an embodiment of the present invention, the spinning speed in step S5 is 5000-6000 rpm / s. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0064] According to an embodiment of the present invention, the spin coating time in step S5 is 20 to 40 seconds. If it is not within this range, the efficiency of the solar cell device will be reduced.

[0065] According to an embodiment of the present invention, the temperature of the fifth annealing treatment is 70-100° C. A temperature outside this range may result in reduced efficiency of the solar cell device.

[0066] According to an embodiment of the present invention, the fifth annealing treatment lasts for 5-10 minutes. If the time is outside this range, the efficiency of the solar cell device will be reduced.

[0067] According to an embodiment of the present invention, the amount of the BCP solution is 50ul.

[0068] According to an embodiment of the present invention, the evaporation in step S6 is performed under vacuum conditions.

[0069] According to an embodiment of the present invention, the evaporation in step S6 is performed by a vacuum coating machine.

[0070] According to an embodiment of the present invention, the vapor deposition in step S6 is performed by thermal evaporation.

[0071] According to an embodiment of the present invention, the metal electrode layer is a silver electrode layer.

[0072] According to an embodiment of the present invention, the thickness of the metal electrode layer is 150-200 nm. If the thickness is not within this range, the efficiency of the solar cell device will be reduced.

[0073] According to the embodiments of the present invention, the present invention has at least one of the following beneficial effects:

[0074] (1) The present invention proposes an inverted perovskite solar cell with UV and water stability and a preparation method thereof. This method for preparing a perovskite solar cell is first proposed by the inventor. Among them, the carboxyl group of FLUO-C3-COOH can undergo Lewis acid-base defect passivation with the perovskite, the surface roughness of the MeO-4PACz:FLUO-C3-COOH hole transport layer is very low, and the nucleation sites on its surface are more dispersed, which is beneficial to the film crystallization of the perovskite and improves the film quality. At the same time, the MeO-4PACz:FLUO-C3-COOH hole transport layer has a very suitable energy level match with the perovskite, which is more conducive to the extraction and transmission of carriers, and the ultraviolet conversion function of FLUO-C3-COOH can convert the ultraviolet short-wave band into long-wave visible light that can be absorbed by the perovskite, thereby improving the overall utilization rate of sunlight, thereby improving the photoelectric conversion efficiency of the perovskite and enhancing the ultraviolet stability of the perovskite solar cell. In addition, the FLUO-C3-COOH on the upper interface of the perovskite 10 The inherent long carbon chain structure of the modified layer itself has hydrophobic properties and can improve the water stability of perovskite solar cells.

[0075] (2) The present invention adopts MeO-4PACz:FLUO-C3-COOH hole transport layer and the perovskite upper interface FLUO-C 10 Modified layer, because the two materials themselves have good inherent stability, and no adverse chemical reactions occur between the interface and the perovskite, the resulting perovskite solar cell has excellent stability, which also lays a good foundation for maintaining long-term stability in practical applications.

[0076] (3) The inverted perovskite solar cell with UV and water stability prepared by the present invention has many advantages such as high conversion efficiency, low defect density, good UV stability and good water stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0078] Figure 1 is the molecular formula of the green fluorescent protein chromophore derivative FLUO-C3-COOH;

[0079] Figure 2 It is a green fluorescent protein chromophore derivative FLUO-C 10 The molecular formula of

[0080] Figure 3 Device structure diagram of inverse perovskite solar cell;

[0081] Figure 4 is a SEM plan view of the perovskite film prepared in Example 1;

[0082] Figure 5 is the XRD pattern of the perovskite film obtained in Example 1;

[0083] Figure 6 Schematic diagram of energy levels of each layer of the inverted perovskite solar cell device in Example 1;

[0084] Figure 7 is a current density-voltage curve of the perovskite solar cell prepared in Example 1;

[0085] Figure 8 is a UV stability curve of the encapsulated perovskite solar cell prepared in Example 1;

[0086] Fig. 9 This is a humidity stability curve of the unencapsulated perovskite solar cell prepared in Example 1. DETAILED DESCRIPTION

[0087] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0088] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0089] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0090] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0091] Example 1

[0092] Preparation of inverse perovskite solar cells (structure such as Figure 1 The steps are as follows:

[0093] (1) Substrate cleaning: Use a glass cutter to cut a large piece of transparent conductive substrate FTO into uniform sizes of 1.5 cm x 1.5 cm, then rinse the FTO surface with deionized water and use an ultrasonic machine to perform ultrasonic treatment for 15 minutes. Then place it in anhydrous ethanol, isopropanol, acetone and anhydrous ethanol for 15 minutes each. After cleaning, place it in anhydrous ethanol solution for storage. When used, blow it dry with high-purity nitrogen and treat it with ultraviolet ozone for 30 minutes.

[0094] (2) Preparation of hole transport layer:

[0095] The first hole transport layer: First, nickel nitrate hexahydrate and ammonia water were stirred for 30 to 60 minutes, then the supernatant was taken out after standing for 30 minutes, and the powder after standing was centrifuged and washed 3 times with deionized water, then vacuum dried in a vacuum drying oven at 100 degrees for 12 hours, and finally the obtained powder was calcined in a muffle furnace for 2 hours at a calcination temperature of 250 to 300 degrees to obtain NiO x Nanoparticle powder. Then NiO x The powder is dispersed and dissolved in clean deionized water to prepare 5-10 mg / ml NiO x Then use a pipette to take out 50ul and evenly drop it on the prepared conductive glass base, use a gel coater to spin coat, the speed is 4000rpm / s, the spin coating time is 30s, and then annealed on a heating table at 150℃ for 30min to obtain NiO x Hole transport layer.

[0096] The second hole transport layer: prepare 1.5 mg / ml MeO-4PACz ethanol solution and 0.05 mg / ml FLUO-C3-COOH ethanol solution respectively, mix and stir according to the amount ratio of FLUO-C3-COOH and MeO-4PACz to obtain a mixed solution of FLUO-C3-COOH and MeO-4PACz of 0.25%. Then use a pipette to take out 50ul and evenly drop it on the prepared nickel oxide hole transport layer, use a gelator to spin coat, the speed is 5000rpm / s, the spin coating time is 30s, and then anneal on a heating table at 150℃ for 30min to obtain a MeO-4PACz:FLUO-C3-COOH hole transport layer.

[0097] (3) Preparation of perovskite light absorbing layer: FAPbI3, CsPbI3 and MAPbBr3 were dissolved in a mixed solvent of DMF and DMSO in a volume ratio of 9:1 to prepare a perovskite precursor solution with a concentration of 1.3 mol / L. After the FAPbI3 solution was fully dissolved, 3% molar concentration of CsPbI3 and 3% molar concentration of MAPbBr3 were added to the FAPbI3 solution, and stirred at a constant speed for 30 to 60 min until uniformly mixed to obtain a perovskite solution. Then, 45 ul of the perovskite precursor solution was taken with a pipette and evenly dropped onto the hole transport layer prepared in step (2). The layer was spin-coated with a spun coating machine at a speed of 5000 rpm / s for 30 s. At the third second before the spin coating, 150 ul of 0.15% mmol / ml FLUO-C 10 The perovskite light-absorbing layer is obtained by extracting the obtained layer with chlorobenzene solution and then transferring the layer to a hot plate and annealing at 100°C for 30 minutes.

[0098] (4) Preparation of electron transport layer: First, weigh 30 mg of PCBM powder sample, then add 1 ml of chlorobenzene solution, stir evenly and filter to prepare 30 mg / ml PCBM solution. Then use a pipette to draw 30 ul and evenly add it to the perovskite light absorption layer prepared in step (3), use a gelling machine to spin coat, the speed is 3000 rpm / s, the spin coating time is 30 s, and then move to a hot plate and anneal at 100 ° C for 10 min to obtain a PCBM electron transport layer.

[0099] (5) Interface modification layer: First, weigh 0.5 mg of BCP powder sample, then add 1 ml of trifluoroethanol solution, stir evenly and filter to prepare 0.5 mg / ml BCP solution. Then use a pipette to draw 50 ul and evenly add it to the electron transport layer prepared in step (4), use a gel coater to spin coat, the speed is 5000 rpm / s, the spin coating time is 30 s, and then move to a hot plate and anneal at 70°C for 5 min to obtain a BCP interface modification layer.

[0100] (6) Electrode evaporation: A layer of silver metal electrode layer is uniformly deposited on the electron transport layer by thermal evaporation under vacuum conditions using a vacuum coating apparatus. The film thickness monitor shows that the thickness of the electron layer is 150 to 200 nm.

[0101] JV test: At AM1.5, the active layer effective area is 0.06cm 2 Under the conditions, the battery was tested to obtain an open circuit voltage of 1.128V and a short circuit current density of 23.45mAcm -2 , the filling factor is 0.806, and the photoelectric conversion efficiency is 21.33%.

[0102] The above embodiments are tested and analyzed below:

[0103] 1. The green fluorescent protein chromophore derivatives FLUO-C3-COOH and FLUO-C used in the perovskite solar cell prepared in Example 1 10 The molecular formulas are Figure 1 , Figure 2 shown.

[0104] 2. The schematic diagram of the device structure of the inverted perovskite solar cell prepared in Example 1 is as follows Figure 3 shown.

[0105] 3. SEM plan view of the perovskite film prepared in Example 1.

[0106] The SEM plan view of the perovskite film prepared in Example 1 is as follows: Figure 4 As shown, the perovskite grains are flat and smooth with good crystallinity.

[0107] 4. XRD spectrum of the perovskite film prepared in Example 1.

[0108] The XRD spectrum of the perovskite film obtained in Example 1 is as follows: Figure 5 As shown in Figure 2, the perovskite deposited on the modified hole transport layer has all the diffraction characteristic peaks that fully match the perovskite of this system, and has good crystallinity, which is also consistent with Figure 4 The test results correspond to .

[0109] 5. Schematic diagram of the energy levels of each layer of the inverted perovskite solar cell device in Example 1.

[0110] The schematic diagram of the energy levels of each layer of the inverted perovskite solar cell device in Example 1 is as follows Figure 6 As shown, it can be seen that the valence band of the modified hole transport layer and the perovskite are very close, which is more conducive to promoting the extraction and transportation of carriers.

[0111] 6. Current density-voltage curve of the perovskite solar cell prepared in Example 1.

[0112] The current density-voltage curve of the perovskite solar cell prepared in Example 1 is as follows: Figure 7 As shown, Example 1 exhibits an open circuit voltage of 1.128 V and a short circuit current density of 23.45 mA cm -2 , a filling factor of 0.806 and a championship efficiency of 21.33%, which is due to the good crystallinity of perovskite and the fast carrier transport between interfaces.

[0113] 7. Ultraviolet stability curve of the encapsulated perovskite solar cell prepared in Example 1.

[0114] In order to eliminate the influence of other environmental factors on the stability of the device, the device is packaged for UV stability testing. The UV stability curve of the packaged perovskite solar cell prepared in Example 1 is shown in FIG. Figure 8 As shown, it can be seen that after continuous irradiation of ultraviolet light for more than 800 hours, the device can still maintain a working efficiency of more than 80%, indicating that the device of Example 1 has excellent ultraviolet stability.

[0115] 8. Humidity stability curve of the encapsulated perovskite solar cell prepared in Example 1.

[0116] The humidity stability curve of the unpackaged perovskite solar cell prepared in Example 1 is as follows: Fig. 9 As shown, it can be seen that under the high humidity conditions of (25±3)°C and (40±5)%RH, the device can still maintain a working efficiency of more than 50% after 200 hours, indicating that the device of Example 1 has excellent humidity stability.

[0117] From the above analysis results, it can be seen that by adding the green fluorescent protein chromophore derivative FLUO-C3-COOH to the hole transport layer MeO-4PACz and adding FLUO-C3-COOH to the extractant chlorobenzene, 10 The processed inverse perovskite solar cells have high power conversion efficiency, excellent UV stability and humidity stability, which also makes them have great potential in practical applications.

[0118] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0119] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An inverted perovskite solar cell, characterized in that: The inverted perovskite solar cell comprises, from bottom to top, a transparent conductive substrate, a first hole transport layer, a second hole transport layer, a perovskite light absorption layer (PVK), an electron transport layer, an interface modification layer and a metal electrode layer, wherein the first hole transport layer comprises NiO x The second hole transport layer includes FLUO-C3-COOH, and the perovskite light absorption layer includes FLUO-C 10 .

2. The inverted perovskite solar cell according to claim 1, characterized in that: The second hole transport layer is a MeO-4PACz film with FLUO-C3-COOH added; Optionally, the perovskite light-absorbing layer is a perovskite light-absorbing layer with a green fluorescent protein chromophore derivative FLUO-C added thereto. 10 APbX3 thin film was prepared by extraction with chlorobenzene solution, where A is Cs + , methylammonium (MA + ) or methyl ether amine (FA + ), X is I - or Br - ; Optionally, the transparent conductive substrate is FTO conductive glass; Optionally, the electron transport layer is PCBM; Optionally, the interface modification layer is BCP; Optionally, the metal electrode layer is a silver electrode layer.

3. A method for preparing an inverse perovskite solar cell, characterized in that: include: S1: NiO x The aqueous solution is spin-coated on a transparent conductive substrate, and a first annealing treatment is performed to obtain a first hole transport layer; S2: Spin-coating a mixed solution of FLUO-C3-COOH and MeO-4PACz on the first hole transport layer, and performing a second annealing treatment to obtain a second hole transport layer; S3: Spin-coat the perovskite solution onto the second hole transport layer with FLUO-C 10 The perovskite light absorbing layer is obtained by extracting the perovskite with a chlorobenzene solution and then performing a third annealing treatment.

4. The method according to claim 3, characterized in that: The method further comprises: S4: spin coating the PCBM solution on the perovskite light absorbing layer, and performing a fourth annealing treatment to obtain an electron transport layer; S5: spin coating the BCP solution on the electron transport layer, and performing a fifth annealing treatment to obtain an interface modification layer; S6: evaporating a metal layer on the interface modification layer to obtain a metal electrode layer.

5. The method according to claim 3, characterized in that: The transparent conductive substrate is pre-cleaned; Optionally, the cleaning process is carried out in the following manner: The transparent conductive substrate is first rinsed with deionized water and ultrasonically treated, and then placed in anhydrous ethanol, isopropanol, acetone and anhydrous ethanol in sequence for ultrasonic treatment; when used, it is blown dry with high-purity nitrogen and then subjected to ultraviolet ozone treatment; Optionally, the transparent conductive substrate is FTO conductive glass; Optionally, the transparent conductive substrate has a size of 1.5 cm x 1.5 cm.

6. The method according to claim 3, characterized in that The NiO x NiO in aqueous solution x The concentration is 5-10 mg / ml; Optionally, the NiO x The aqueous solution was prepared as follows: Nickel nitrate hexahydrate and ammonia water were dissolved in deionized water and stirred for reaction, and the product was washed three times by centrifugation with deionized water. The obtained product was vacuum dried and finally NiO was obtained in a muffle furnace. x Powder, NiO x The nanoparticles are dispersed in deionized water at a concentration of 5 to 10 mg / ml to obtain the NiO x Aqueous solution; Optionally, the temperature of the muffle furnace is 250-300°C; Optionally, the speed of the spinning in step S1 is 3000-5000 rpm / s; Optionally, the spinning time in step S1 is 30 to 60 seconds; Optionally, the temperature of the first annealing treatment is 100-200°C; Optionally, the first annealing treatment time is 30 min; Optionally, the NiO x The amount of aqueous solution used is 40 to 60 ul.

7. The method according to claim 3, characterized in that The molar ratio of FLUO-C3-COOH to MeO-4PACz in the mixed solution of FLUO-C3-COOH and MeO-4PACz is 0.25%; Optionally, the mixed solution of FLUO-C3-COOH and MeO-4PACz is prepared by the following method: Prepare ethanol solutions of FLUO-C3-COOH and MeO-4PACz of certain concentrations respectively, mix and stir according to the molar ratio of FLUO-C3-COOH to MeO-4PACz of 0.25% to obtain the mixed solution of FLUO-C3-COOH and MeO-4PACz; Optionally, the speed of the spinning in step S2 is 3000-5000 rpm / s; Optionally, the spinning time in step S2 is 30 to 60 seconds; Optionally, the temperature of the second annealing treatment is 100-150°C; Optionally, the second annealing treatment time is 10-30min; Optionally, the amount of the mixed solution of FLUO-C3-COOH and MeO-4PACz is 40-50 ul.

8. The method according to claim 3, characterized in that The perovskite solution includes FAPbI3, CsPbI3 and MAPbBr3; Optionally, the perovskite solution is prepared by: Dissolve FAPbI3, CsPbI3 and MAPbBr3 in a mixed solvent of DMF and DMSO in a volume ratio of 9:1, respectively, to prepare a perovskite precursor solution with a concentration of 1.3 mol / L, and add 3% molar concentration of CsPbI3 and 3% molar concentration of MAPbBr3 to the FAPbI3 solution after the precursors are fully dissolved, to obtain the perovskite solution; Optionally, the speed of the spinning in step S3 is 4000-6000 rpm / s; Optionally, the spinning time in step S3 is 20 to 40 seconds; Optionally, in step S3, 150 to 200 μl of 0.15% mmol / ml FLUO-C is evenly and rapidly added 1 to 5 seconds before the spin coating. 10 chlorobenzene solution for extraction, and then the perovskite mesophase film is transferred to a third annealing treatment; Optionally, the temperature of the third annealing treatment is 100° C.; Optionally, the third annealing treatment lasts for 10 to 30 minutes; Optionally, the amount of the perovskite solution is 45ul.

9. The method according to claim 4, characterized in that The concentration of the PCBM solution is 20-40 mg / ml; Optionally, the PCBM solution is obtained by dissolving PCBM in a chlorobenzene solution; Optionally, the speed of the spinning in step S4 is 2000-3000 rpm / s; Optionally, the spinning time in step S4 is 20 to 40 seconds; Optionally, the temperature of the fourth annealing treatment is 70-100° C.; Optionally, the fourth annealing treatment is performed for 10-20 minutes; Optionally, the amount of the PCBM solution is 30ul.

10. The method according to claim 4, characterized in that The concentration of the BCP solution is 0.5-1 mg / ml; Optionally, the BCP solution is obtained by dissolving BCP in trifluoroethanol; Optionally, the speed of the spinning in step S5 is 5000-6000 rpm / s; Optionally, the spinning time in step S5 is 20 to 40 seconds; Optionally, the temperature of the fifth annealing treatment is 70-100° C.; Optionally, the fifth annealing treatment is performed for 5-10 minutes; Optionally, the amount of the BCP solution is 50ul; Optionally, the evaporation in step S6 is performed under vacuum conditions; Optionally, the evaporation in step S6 is performed by a vacuum coating machine; Optionally, the evaporation in step S6 is performed by thermal evaporation; Optionally, the metal electrode layer is a silver electrode layer; Optionally, the thickness of the metal electrode layer is 150-200 nm.

Citation Information

Patent Citations

  • Quasi-two-dimensional perovskite solar cell of trans-plane structure and preparation method thereof

    CN113659079A

  • Perovskite solar cell and preparation method thereof

    CN115568237A

  • Energy storage perovskite solar cell internally integrated with anti-ultraviolet nano fluorescent powder

    CN116744703A

  • Processing in humid air of efficient perovskite solar cells based on polymerizable ionic liquids and salts

    WO2021209120A1